Energy exchange and water budget partitioning in a boreal minerogenic mire - Peichl, Matthias; Sagerfors, Jörgen; Lindroth, Anders; Buffam, Ishi; Grelle, Achim; Klemedtsson, Leif; Laudon, Hjalmar; Nilsson, Mats B. (Journal of geophysical research. Biogeosciences, 2013)
This study investigated patterns and controls of the seasonal and inter‐annual variations in energy fluxes (i.e., sensible heat, H, and latent heat, λE) and partitioning of the water budget (i.e., precipitation, P; evapotranspiration, ET; discharge, Q; and soil water storage, ∆S) over five years (2001–2005) in a boreal oligotrophic fen in northern Sweden based on continuous eddy covariance, water table level (WTL), and weir measurements. For the growing season (May 1 to September 31), the 5 year averages (± standard deviation) of the midday (10:00 to 14:00 h) Bowen ratio (β, i.e., H/λE) was 0.86 ± 0.08. Seasonal and inter‐annual variability of β was mainly driven by λE which itself was strongly controlled by both weather (i.e., vapor pressure deficit, D, and net radiation, Rn) and physiological parameters (i.e., surface resistance). During the growing season, surface resistance largely exceeded aerodynamic resistance, which together with low mean values of the actual ET to potential ET ratio (0.55 ± 0.05) and Priestley‐Taylor α (0.89) suggests significant physiological constrains on ET in this well‐watered fen. Among the water budget components, the inter‐annual variability of ET was lower (199 to 298 mm) compared to Q (225 to 752 mm), with each accounting on average for 34 and 65% of the ecosystem water loss, respectively. The fraction of P expended into ET was negatively correlated to P and positively to Rn. Although a decrease in WTL caused a reduction of the surface conductance, the overall effect of WTL on ET was limited. Non‐growing season (October 1 to April 30) fluxes of H, λE, and Q were significant representing on average −67%, 13%, and 61%, respectively, of their growing season sums (negative sign indicates opposite flux direction between the two seasons). Overall, our findings suggest that plant functional type composition, P and Rn dynamics (i.e., amount and timing) were the major controls on the partitioning of the mire energy and water budgets. This has important implications for the regional climate as well as for ecosystem development, nutrient, and carbon dynamics. Key Points ET was driven by VPD and radiation but not by WTLP, Rn, and concurrent WTL dynamics regulated mire water budget partitioningNon‐growing season energy and water exchange was significant in this boreal mire